The Heme Transporter HtsABC of Group A Streptococcus Contributes to Virulence and Innate Immune Evasion in Murine Skin Infections - Song, Yingli; Zhang, Xiaolan; Cai, Minghui; Lv, Chunmei; Zhao, Yuan; Wei, Deqin; Zhu, Hui (Frontiers in Microbiology, 2018)
Group A Streptococcus (GAS) requires iron for growth, and heme is an important source of iron for GAS. Streptococcus heme transporter A (HtsA) is the lipoprotein component of the GAS heme-specific ABC transporter (HtsABC). The objective of this study is to examine the contribution of HtsABC to virulence and host interaction of hypervirulent M1T1 GAS using an isogenic htsA deletion mutant (ΔhtsA). The htsA deletion exhibited a significantly increased survival rate, reduced skin lesion size and reduced systemic GAS dissemination in comparison to the wild type strain. The htsA deletion also decreased the GAS adhesion rate to Hep-2 cells, the survival in human blood and rat neutrophils, and increased the production of cytokine IL-1β, IL-6 and TNF-α levels in air pouch exudate of a mouse model of subcutaneous infection. Complementation of ΔhtsA restored the wild type phenotype. These findings support that the htsA gene is required for GAS virulence and that the htsA deletion augments host innate immune responses.